2021
DOI: 10.1177/13621688211058245
|View full text |Cite
|
Sign up to set email alerts
|

Channelling discomfort through the arts: A Covid-19 case study through an intercultural telecollaboration project

Abstract: In this article we argue, in the context of the current dominance of the performative and instrumental drives characterizing the accountable university, that language and intercultural communication education in universities should also be humanistic, addressing ‘discomforting themes’ to sensitize students to issues of human suffering and engage them in constructive and creative responses to that suffering. We suggest that arts-based methods can be used and illustrate this with an intercultural telecollaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
0
14
0
1
Order By: Relevance
“…Another major line of research has focused on the design and implementation of pedagogical activities to facilitate peer interaction and/or teacher-student communication in online teaching. These studies discuss the value of telecollaboration among students through the building of virtual literature circles ( Ferdiansyah, Ridho, Sembilan, Sembilan, & Zahro, 2020 ) and the creation of intercultural projects ( Porto, Golubeva, & Byram, in press ). The notion of telecollaboration-oriented pedagogy has also been integrated into pre-service language teacher education for pedagogical task design ( Ekin, Balaman & Bademkorkmaz, in press ).…”
Section: Research On Online Language Teaching and Learningmentioning
confidence: 99%
“…Another major line of research has focused on the design and implementation of pedagogical activities to facilitate peer interaction and/or teacher-student communication in online teaching. These studies discuss the value of telecollaboration among students through the building of virtual literature circles ( Ferdiansyah, Ridho, Sembilan, Sembilan, & Zahro, 2020 ) and the creation of intercultural projects ( Porto, Golubeva, & Byram, in press ). The notion of telecollaboration-oriented pedagogy has also been integrated into pre-service language teacher education for pedagogical task design ( Ekin, Balaman & Bademkorkmaz, in press ).…”
Section: Research On Online Language Teaching and Learningmentioning
confidence: 99%
“…Newer developments have addressed important societal change and the beneficial role that VE can play; O'Dowd (2020) found that VE can be a vehicle for promoting global citizenship's core values, such as respect for diversity and solidarity for humanity. It has also been employed as a medium for students to process trauma arising from the Covid-19 crisis (González-Ceballos et al, 2021;Porto et al, 2021), and for working through international conflicts and controversies (Watanabe, 2020).…”
Section: Virtual Exchangementioning
confidence: 99%
“…As I was promoted to teaching positions with increased decision-making responsibilities in that course over these 25 years, I introduced changes at different times such as the move from product to process writing and the use of genre-based pedagogies, intercultural perspectives in language education with a multiliteracies, multimodal, arts-based and translingual approach, a content and language integrated learning (CLIL) orientation using literature as a basis to address citizenship and human rights concerns, and an intercultural citizenship perspective connecting language learning and students' engagement in social and civic action in the community during their college education (Byram, 2014;Byram et al, 2017). My co-authored article in this special issue (Porto, Golubeva & Byram, 2021, this issue) illustrates these orientations.…”
Section: Contextual Background To This Special Issuementioning
confidence: 99%